Religious coping in patients with severe substance use disorders receiving acute inpatient detoxification. (24th August 2017) - Medlock, Morgan M.; Rosmarin, David H.; Connery, Hilary S.; Griffin, Margaret L.; Weiss, Roger D.; Karakula, Sterling L.; McHugh, R.Kathryn
Abstract : Background and Objectives: Religious coping, one of the most widely studied components of spirituality among psychiatric populations, has rarely been addressed in patients with severe substance use disorders (SUD). The aim of our study was to elucidate whether religious coping is related to symptom expression and mutual‐help participation. Methods: Self‐reported religious coping was assessed in individuals sequentially admitted to a private psychiatric hospital for inpatient detoxification. Target symptoms of SUD included severity of substance use prior to admission and craving during detoxification. Three hundred thirty‐one patients (68.6% male) participated in the survey; mean age was 38.0 years, and primary presenting diagnosis was most commonly alcohol use disorder ( n  = 202; 61%), followed by opioid use disorder ( n  = 119; 36%). Results: Positive religious coping was associated with significantly greater mutual‐help participation, fewer days of drug use prior to admission, and was modestly, yet significantly associated with lower drug craving. Negative religious coping was associated with lower confidence in the ability to remain abstinent post‐discharge and higher drug craving. Conclusions: Consistent with hypotheses, greater positive religious coping was associated with greater mutual‐help participation, lower severity of pre‐admission drug use, and lower substance craving during detoxification. Use of positive religious coping may modify the course of SUD recovery by promoting engagement in mutual‐help activities. Scientific Significance: The findings of this study suggest that positive and negative religious coping are linked with several key SUD recovery variables. Further research to replicate this finding and to assess mechanisms within this potential association is warranted. (Am J Addict 2017;26:744–750)